KONSUMSI NUTRISI DENGAN STATUS GIZI DI MASA PANDEMI - Dewi, Novita; Maemunah, Neni; Putri, Ronasari Mahaji (Universitas Tribhuwana Tunggadewi, 2021)
Nutrition includes various components of nutrients such as carbohydrates, proteins, fats and minerals. These components in the body undergo metabolism to be stored and used by the body, so the adequacy of these components determines nutritional status, especially in the pandemic era it is known that all aspects of life including students and their families are also experiencing global effects, even in consuming nutrients. Nutritional status can be measured by various parameters, one of which is using Body Mass Index (BMI) by comparing body weight and height. The purpose of the study was to determine the correlation between nutrient consumption and body mass index during the pandemic. Correlation and cross-sectional is the design of this study. The population of professional students and their families, the sample is 44 respondents, using purposive sampling. The instrument used is a questionnaire. with bivariate analysis in the form of chisqure. The results showed that most of the nutritional consumption was 70.5% (31 people) in the good category, the nutritional status was mostly 56.8% (25 people) with normal nutritional status, the results of chiquare p = 0.125 p value 0.05, meaning that there was a relationship between nutritional consumption and body mass index obtained 0.125.